ETHICAL AND DISCIPLINE RESPONSIBILITY OF POLICE MEMBERS INVOLVED IN DRUG ABUSE FROM THE POLICE MERANTI ISLANDS - Yohanes Janter Lumban Toruan; Fahmi; Rudi Pardede (JILPR Journal Indonesia Law and Policy Review, 2026)
Narcotics offenses constitute serious violations under the Code of Ethics of the Indonesian National Police (KEPP). Accordingly, police officers who are proven to have committed such criminal acts and whose cases have been decided by a court with final and binding legal force may be subsequently recommended to receive administrative sanctions in the form of Dishonorable Discharge (PTDH). The purpose of this study is to analyze the legal regulation of ethical and disciplinary responsibility of police officers involved in narcotics abuse at the Pulau Meranti Police Resort. This research employs a sociological legal research method. Based on the research findings, it is evident that the involvement of police officers in narcotics abuse constitutes a serious violation with multilayered legal implications, encompassing criminal liability, disciplinary sanctions, and professional ethical responsibility. Members of the Indonesian National Police are bound by legal and moral obligations to uphold the law, adhere to professional ethics, and maintain the honor and dignity of the police institution, as mandated by Law Number 2 of 2002 on the Indonesian National Police, Government Regulation Number 2 of 2003 concerning Police Disciplinary Regulations, and Regulation of the Chief of the Indonesian National Police Number 7 of 2022 on the Police Professional Code of Ethics. However, this study also reveals that cases involving police officers in narcotics abuse continue to occur annually, including within the jurisdiction of the Pulau Meranti Police Resort. As a result, the persistence of such violations underscores that the enforcement of ethical and disciplinary sanctions has tended to be repressive in nature and has not fully addressed preventive and comprehensive guidance aspects.